Predictability, Severity and Causality Assessment of Adverse Drug Reactions Reported at a Tertiary Care Hospital in Belagavi, North Karnataka: A Prospective Observational Study - Reddy, Mandati Santhosh; Kini, Pratiksha Nagesh; Ganachari, Madiwalayya Shivkantayya (International Journal of Pharmaceutical Investigation, 2025)
Introduction Adverse Drug Reactions (ADRs) present major challenges in healthcare, contributing significantly to hospital admissions and impacting a large number of inpatients. Monitoring ADRs often relies on electronic health records or specialized surveillance programs. Issues such as underreporting and delays highlight the need for robust ADR tracking, while advancements in technology offer new opportunities to enhance this process. Effective ADR monitoring and analysis are essential for ensuring patient safety and supporting regulatory decision-making. Objectives To assess the predictability, severity and causality of ADRs using various scales. Materials and Methods A Prospective Observational Study was conducted for a year at the ADR Monitoring Center (AMC) in a tertiary care hospital at Belagavi, under the PvPI. ADRs reported from both outpatient and inpatient departments were included, except those due to drug poisoning, blood products and alternative medicines. Data were collected and evaluated for causality, predictability and severity using appropriate scales. Descriptive statistics were employed for analysis. Results A total of 706 ADRs were reported, with 56% in adults and 24% in the elderly. Males constituted 51.2% of the cases. Severity assessment using the Hartwig and Siegel Scale showed 63% mild, 35% moderate and 2% severe ADRs. Predictability assessment revealed 74% were predictable. Causality assessment based on the WHO-UMC scale classified 50.2% as probable, 38.9% as possible and 10.3% as certain. Gastrointestinal disorders were the most common ADRs (19.87%), followed by skin and subcutaneous tissue disorders (14.74%). Drug withdrawal was the most common action taken (52.92%), with 39.6% fully recovered patients. Conclusion The study underscores the importance of comprehensive ADR monitoring and management. High predictability suggests many ADRs can be anticipated and prevented through meticulous risk assessment and patient monitoring. Personalized approaches to drug therapy and holistic patient monitoring are crucial to ensure patient safety and well-being.
Keywords: Adverse Drug Reactions; Causality; Hartwig and Siegel Scale; Predictability; Severity